An Efficient Mutual Exclusion Algorithm for Redundant Resources in Distributed Operating Systems - Ramos, Marco Antonio Dantas; Macêdo, Raimundo José de Araújo; Blagojevic, Anne (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2012)
Increasing demand for distributed applications raises the need for more reliable control of shared resources among distributed processes. Because of the inherent redundancy of distributed systems, algorithms for critical section access must consider not only the shared resource but also the possibility of redundancy of such a resource. These algorithms are thus known as distributed k-mutex since they control access to k versions of the same shared resource. The inherent uncertainties of distributed systems, like unbounded message transfer delay and the difficulty to detect failures, make the distributed k-mutex problem hard to solve. In this paper, we present a k-mutex algorithm that runs under the partitioned synchronous model, which have recently been formalized, which guarantee liveness (termination) without being restrictive as those conventional solutions of synchronous systems. We complement the presentation of our algorithm with related correctness proofs and simulations that show the efficacy of the proposed solution.